ISLAMIC EDUCATION DEVELOPMENT BASED ON UNITY OF SCIENCES PARADIGM - Junaedi, Mahfud; Wijaya, Mirza Mahbub (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The focus of this research lies in the philosophical analysis of Islamic education based on the Unity of Sciences paradigm. So far, no researcher has studied this issue specifically and comprehensively. This study uses a philosophical and phenomenological approach of library research. The finding shows that the development of managed Islamic education has both human and divine potential. Unity of Sciences has become the basis for creating a balanced Islamic education paradigm with humanization and spiritualization strategies. Therefore, development of Islamic education based on Unity of Sciences can produce modern scientists who are religious and not anti-local culture. Thus, this paradigm encourages scientists to dialogue and reciprocally lead someone closer and closer to God, the Most True (al-á¸¤aqq). This paradigm is implemented into the curriculum at State Islamic University (UIN) Walisongo Semarang.